Antropometri Pengguna dan Nilai Ergonomis Bangunan Bale Sakenem Pada Rumah Tinggal Tradisional Bali - I Wayan Parwata (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2019)
Traditional architecture is an architecture that is constructed based on or in accordance with the rules of the tradition adopted (Saliya, 2015). Traditional Balinese architecture is built following the layout, spatial layout and layout based on the concept of Asta Kosala Kosali and Asta Bumi (son, 1984). The architecture of traditional Balinese dwelling house is one of Indonesia's architectural works that need to be preserved and developed without eliminating the rules of local wisdom in Bali. In the setting of traditional Balinese homes in general has some period of building, among others: Holy place, Bale Meten (Bale Daje), Bale Dangin, Bale Dauh, Kitchen (Paon), and Jineng/Klumpu (place to store rice). The concept in traditional Balinese architecture is one of the concepts used in the technique of housing arrangement based on the anatomy of the Human Body (anthropometry) owner. The study uses the quasi experiment design. At this stage, modelling building "Sakenem" in the village of central Singapadu. In this study, the size made for the modeling of Bale Sakenem buildings has been adapted to the antopometry of the users to obtain the size of the height of Saka, Bale-bale, and body that meets the comfort of the user's antopometric. After the modeling and comfort assessment, the results obtained positive and significant comfort assessment of all aspects of the high Saka, Bale-bale height, and the height of the trunk in the Bale Sakenem building in the village of Singapadu Tengah.